2008
DOI: 10.1016/j.mad.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Age-related activation of mitochondrial caspase-independent apoptotic signaling in rat gastrocnemius muscle

Abstract: Mitochondria-mediated apoptosis represents a central process driving age-related muscle loss. However, the temporal relation between mitochondrial apoptotic signaling and sarcopenia as well as the regulation of release of pro-apoptotic factors from the mitochondria has not been elucidated. In this study, we investigated mitochondrial apoptotic signaling in skeletal muscle of rats across a wide age range. We also investigated whether mitochondrial-driven apoptosis was accompanied by changes in the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
149
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 50 publications
12
149
0
Order By: Relevance
“…Interestingly, elevated mitochondrial levels of CyPD relative to ANT and VDAC were detected in the gastrocnemius muscle of very old rats [18]. This finding underlines the major role postulated for CyPD in the formation of the mPTP, and suggests a higher susceptibility to mPTP opening at an older age.…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 91%
See 3 more Smart Citations
“…Interestingly, elevated mitochondrial levels of CyPD relative to ANT and VDAC were detected in the gastrocnemius muscle of very old rats [18]. This finding underlines the major role postulated for CyPD in the formation of the mPTP, and suggests a higher susceptibility to mPTP opening at an older age.…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 91%
“…Accordingly, levels of Apaf-1 [13,46,60], active caspase-9 content [52,54,60], and caspase-9 proteolytic activity [46] were also found to be higher in aged muscles compared to young controls. However, other studies did not observe increases in cytosolic cytochrome c and/or caspase-9 expression in skeletal muscles of old rats [12,13,18,49]. Surprisingly, it was observed that gene expression levels of Apaf-1 were even reduced in the plantaris of old and senescent rats relative to younger controls [50].…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 96%
See 2 more Smart Citations
“…An increase in the ratio between CypD and ANT with aging was observed. This may contribute to higher susceptibility to mPTP opening (Marzetti et al., 2008) and to the reduction in affinity of ANT for CypD. An increased phospho‐GSK‐3β binding to ANT was suggested to be responsible for the inhibition of mPTP opening (Miura & Tanno, 2010; Nishihara et al., 2007).…”
Section: Putative Molecular Components Of Mptp and Agingmentioning
confidence: 99%